2000
DOI: 10.1097/00002030-200003100-00015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of highly active antiretroviral therapy on cervicovaginal HIV-1 RNA

Abstract: The cervicovaginal HIV-1 RNA level was positively correlated with plasma HIV-1 RNA and negatively with the CD4 cell count. The use of HAART was significantly associated with below-detectable levels of HIV-1 RNA in both plasma and the genital tract. HIV-1 RNA suppression in the genital tract may occur rapidly after initiating therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
99
0
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(105 citation statements)
references
References 24 publications
4
99
0
2
Order By: Relevance
“…As seen in humans, there was an overall significant positive linear correlation between the viral load in plasma and CVS (Spearman's correlation coefficient = 0.55 [95% CI, 0.36-0.69, P < 0.001, n = 51]) (Figure 3E and refs. 31,(39)(40)(41)(42).…”
Section: Reconstitution Of the Frt Of Blt Mice With Human Cd4mentioning
confidence: 99%
“…As seen in humans, there was an overall significant positive linear correlation between the viral load in plasma and CVS (Spearman's correlation coefficient = 0.55 [95% CI, 0.36-0.69, P < 0.001, n = 51]) (Figure 3E and refs. 31,(39)(40)(41)(42).…”
Section: Reconstitution Of the Frt Of Blt Mice With Human Cd4mentioning
confidence: 99%
“…[2][3][4][5] This is evidenced by data obtained from animal's studies 6,7 and a case control study of post exposure prophylaxis following needle stick injury in health care settings. 8 According to the centers for diseases control and prevention (CDC), individuals who took zidovudine monotherapy following occupational exposure were less likely to acquire HIV as compared to those who did not take medication.…”
mentioning
confidence: 99%
“…In a study conducted in the United States to evaluate the time course and magnitude of decay in cervical and vaginal HIV-1 shedding as women initiate HAART [30], genital HIV-1 shedding decreased rapidly after HAART initiation, which is consistent with a rapid decrease in infectivity. In a study from Kenya assessing the effect of acquisition and treatment of cervical infection on genital HIV shedding in women on HAART [31], most cervical HIV-1 RNA concentrations were near the threshold for detection, which suggested that HIV infectivity remains low, and thus HAART reduces genital HIV-1 shedding. Another study [32] found a positive correlation between HIV-1 RNA levels and plasma HIV-1 RNA and a negative correlation with the CD4 cell count.…”
Section: Discussionmentioning
confidence: 99%